PENGARUH COMPENSATION TERHADAP EMPLOYEE ENGAGEMENT DAN DAMPAKNYA PADA EMPLOYEE PERFORMANCE PADA PERUSAHAAN CAFÉ PREMIUM DI KABUPATEN PASURUAN - Fandy Ardiansyah; Budiono Budiono (Jurnal Ilmu Manajemen, 2022)
In a company, employee performance is one of the determining components of company performance. Several factors can affect employee performance, such as compensation, job satisfaction, and employee engagement. A kind of company that has been popular in recent times is a coffee shop. It is evidenced by the increase in coffee shops and domestic coffee consumption over the last three years. This study aims to analyze the effect of compensation on employee engagement and its impact on employees who work at premium coffee shops. This study uses a type of causality research that uses quantitative methods. The sampling technique used is accidental sampling with respondents as many as 91 employees of Premium coffee shops in Pasuruan Regency. Statistical analysis in this study used the Structural Equation Model (SEM). The results of the study state that compensation has a significant and positive effect on employee engagement because a higher salary will make employee engagement higher. Employee engagement has a substantial and positive effect on employee performance because of the greater attention of the employee to the company; their performance will be better. In contrast, payment has no significant impact on employee performance because low compensation has not made employees perform poorly. The coffee shops managers must pay attention to the level of compensation and employee welfare to increase employee engagement and improve performance.